2009
DOI: 10.1177/0961203308096661
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus pregnancies: a case series from a tertiary, East Malaysian hospital

Abstract: We performed a retrospective study of all systemic lupus erythematosus (SLE) pregnancies during a two-year period (2006-2007) to describe the clinical features, maternal and foetal outcomes in our centre. There were 17 pregnancies in 16 women with SLE. Our patients have a mean age of 28.31 years (SD 5.24) and a mean disease duration of 38.62 months (SD 38.03). Our patients have complicated pregnancies: 35.3% have SLE flares, 21.1% have preeclampsia and 47.4% needed caesarean sections. There were 15.8% foetal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
(40 reference statements)
1
4
0
2
Order By: Relevance
“…Consistent with prior reports, newly-diagnosed SLE during pregnancy was more likely to involve the kidney and platelets. [17][18][19] It was previously reported that the abortion rate in pregnant patients with SLE was 8 to 24%, 20 which was comparable to the 24.5% in this study. The incidence of premature births was 26.7%.…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with prior reports, newly-diagnosed SLE during pregnancy was more likely to involve the kidney and platelets. [17][18][19] It was previously reported that the abortion rate in pregnant patients with SLE was 8 to 24%, 20 which was comparable to the 24.5% in this study. The incidence of premature births was 26.7%.…”
Section: Discussionsupporting
confidence: 76%
“…Many studies support maternal and pregnancy benefit of HCQ and low risk for mother and fetus . Potential contraindications include allergy, adverse side effects, or intolerance.…”
Section: Results/recommendationsmentioning
confidence: 99%
“…[8][9]12 Unfavorable pregnancy outcome has been reported to be associated with specific factors which include active disease during pregnancy, renal involvement, hypocomplementemia, and antibodies to Ro/SSA, etc. 6,9,12 There are a few reports on pregnancies in SLE patients from Asia, 13 but pregnancy studies in patients with SLE from the Middle East are negligible. However, a report has been published very recently from western Saudi Arabia which deals with pregnancies in a small subset of SLE patients.…”
Section: Introductionmentioning
confidence: 99%